Análise das vivências e percepções da violência na adolescência e sua relação com os Fatores Socioeconômicos e Demográficos - Dálian Cristina Rocha (2018)
Introduction: To comprehend violence as a social and historical phenomenon, it is fundamental to study its social determinants in a complex and dialectical way, considering how it relates with the lived moment, interests and values of their time and respective society. Violence is one of the main causes of morbidity among teenagers. Therefore, it is considered the importance of the understanding about how the association of socioeconomic and demographic individuals and the involvement of young people in situations of violence. Methodology: field research with observational, analytical, cross-sectional design. It is an extract from the populationbased survey "Health and violence: subsidies for the formulation of public policies in health promotion and violence prevention" The sample was composed of teenagers in between the ages 10 and 19 years old, living in the cities of Belo Horizonte and Betim. The instrument of data collection was self-administered questionnaire. Based on the thematic axis "violence" were developed the indicators of experience and perception of violence and for the socioeconomic and demographic characterization were used variables of different thematic axes. Results: in the univariate analysis, 60.4% of the adolescents presented a high life expectancy indicator and 47.1% presented an indicator for high perception. The high indicator of experience also suggests a high indicator of perception and vice versa. With the bivariate analysis it was possible to observe the relationship between the indicators and the socioeconomic and demographic variables. The multivariate analysis revealed a greater association between white women and those with low perception and experience of violence. Non-white women are associated more with high perception and experience, as well as with those who have low perception and high living. White men with low perception and experience, while non-whites, were more associated with high perception and low experience. Higher association among those interviewed with family income up to 2 minimum wages and high perception and low living, family income above 4 minimum wages more with high perception and high experience. Higher association between school dropout and/or family unemployment with high perception and high experience. School failure associated more with high perception of violence and low living. Living with father and mother and believing in God were more associated with low perception and experience, and with low perception and high living. Conclusion: It stands out the importance to understand the individual factors, collective factors and how they exert influence in the teenager’s experiences of violence. Approaches such as those carried out by this study, help in the understanding of this phenomenon and facilitate ways to prevent this phenomenon.